Policy Implementation of Village Boundary Confirmation and Determination: A Qualitative Study of Administrative Boundary Governance in Two Adjacent Villages - Andre R Sinaga; Devie S. R. Siwij; Steven V. Tarore (JR Education, 2026)
This article analyzes the implementation of village boundary confirmation and determination policy in two adjacent villages that experienced a prolonged administrative boundary dispute. The study is positioned within public administration because village boundaries are not merely cartographic lines; they define legal authority, service coverage, development planning, asset governance, and social harmony. A qualitative descriptive design was used, supported by interviews, observation, and documentation. The analysis applied the policy implementation perspective of George C. Edward III, especially communication, resources, disposition, and bureaucratic structure. The findings show that the implementation process has formally followed the logic of the Minister of Home Affairs Regulation Number 45 of 2016, including document inventory, technical tracing, kartometric analysis, mapping, facilitation, and deliberation. However, the process has not yet produced a final and binding boundary decision. The main obstacles include different interpretations of the same legal basis, fragmented historical and spatial data, limited technical mapping capacity at the village level, inadequate integration of geospatial information, strong community attachment to historical claims, and coordination that has not yet generated a mutually accepted agreement. The article argues that boundary policy implementation requires not only procedural compliance but also an integrated governance mechanism that combines legal validation, geospatial data management, participatory deliberation, and authoritative decision-making. The study contributes to public administration by showing that effective boundary governance depends on the interaction between policy clarity, technical capacity, collaborative communication, and institutional authority.